Phenomenological–based strategy for the Gurson-Tvergaard-Needleman model parameters identification - R. Bensaada; A. Imad; T. Kanit; A. EL Moumen; M. Almansba; A. Saouab (Applications in Engineering Science, 2025)
The Gurson–Tvergaard–Needleman GTN model is widely used for ductile fracture simulations. However, the selection of its parameters is often done randomly to reproduce the experimental data without considering the physical consistency of the set of parameters selected. This contribution is dedicated to the relevance of the GTN model parameters selection using a consistent method based on the ductile fracture phenomenology.The proposed method consists of the prioritization of the void volume fraction parameters in accordance with the kinetics of the ductile fracture phenomenon, while the nucleation and fracture parameters are chosen in conformity to the strength to fracture. Experimental data obtained from 12NC6 steel is used through various tests. Axisymmetric notched and compact tension specimens are used. The interest of the use of this variety of tests lies in the variation of stress triaxiality ratio given its widely proven importance in the ductile fracture process. The strategy is finally applied to a CT (Compact-Tension) test simulation. Satisfactory result are achieved while the number of attempts to reproduce the experimental data is considerably reduced, this lead to considerable saving of computational time.